Petrology of volcanic rocks from Khan- Ghohestan area (Northeast of Birjand, East of Iran) - Mohammad Hossein Yousefzadeh; Fatemeh Fanoodi; Golamreza Fotoohirad (پترولوژی, 2018)
The Tertiary volcanic rocks in the Khan area have vast outcrops and alternatively include of lava and pyroclastic rocks. The composition of most lavas are dacite, andesite and basaltic trachyandsite with medium potassium calc-alkaline nature. The most phenocrysts in these rocks include oscillatory chemical zonal plagioclases with andesine to oligoclase composition, hornblende, pyroxene, and quartz with apatite as a common accessory mineral. The most important textures of these rocks are porphyritic with microgranular and microlitic matrix, glomeroporphyritic, flow and vesicular. The essential mineral textures are sieve, gulf corrosion and zoning, which point to inequilibrium and magma mixing processes during magma ascension. Depletion of Ti and Nb of these rocks can be indication of magmatism of subduction zone.Nb negative anomaly in the rocks under study is indicator of continental rocks and may be related to crustal involvement in magmatic processes. Based on normalized spider diagrams for rare and rare earth elements, depletion of incompatible elements with high ionic potential such as Ti, Nb, P and Zr in the studied samples can be attributed to magmatism of subduction zone and may be ascribed to the presence of an enriched and metasomatized mantle source by subduction processes and also the occurrence of amphibole and high oxygen fugacity in the magma. Based on the interpretation of tectono-magmatic diagrams, the study volcanic rocks are related to active continental margin subduction zone.